Дослідження Малокопанського комплексу в 2009 р. - Котигорошко, В.Г.; Прохненко, І.А.; Мойжес, В.В. (Археологічні дослідження в Україні, 2010)
Excavations at Mali Kopani Dacian complex (hill-fort and burial ground) concentrated at the territory of necropolis in Chellenytsya tract. At the area of 1580 m2 six underground cremations were discovered. Significant amount of arms, riders’ equipment, harness, adornments, and details of clothes dated by the first half of the 1st c. BC were found beyond the graves.